Implementasi Strategi Pembelajaran Edutainment Berbasis Karakter dalam Pendidikan Agama Islam - Mochammad Rizal Ramadhan (Program Studi Pendidikan Agama Islam (PAI) Sekolah Tinggi Agama Islam Al Azhar, 2020)
Implementation of edutainment learning strategy character based in islamic education. Strategy has an important role in the learning process, in islamic religious education the strategy needed is in accordance with the needs that support the learning undertaken. The impression of islamic education is a lesson that is read and only consists of texts that can only be read that will change according to the strategies implemented in the learning process. The edutainment concept applied in islamic religious education learning can provide the best solution to strengthen the character of students. Because, in this concept it is about providing space to be more active and develop students' creativity. Character is the main target in learning islam, because participants attended the process are expected to have good character. Not only good, but also has the strength and long-lasting is also applied in everyday life. In this paper, we will discuss the implementation of character-based edutainment learning strategies in islamic religious education learning. Through this strategy, the creativity of students in learning will develop.